Investigation the Abuse of Family with Rural Elderly in ilam in 2019 - Masoumeh Otaghi1, Forouzan Kavarizadeh2 , Mohsen Nikvand3 , Ali Khorshidi4,6, Seyed Rahmatollah Mous (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: ABUSE is among the meaning of deprivation of human rights and grandeur that appear as negligence, authority negation, financial exploitation, physical and psychological vexations, and rejection. This study was done to investigate the ABUSE of family with rural elderly in the city of Ivan in 2019. Methods: 92 elderlies who lived in two villages of the city of Ivan in 2019 were selected by stage cluster sampling in this descriptive cross-sectional study. An 8-point Iranian questionnaire of ABUSE related to the elderly in the family and with scores ranging from 0 to 100 was the research tool. Data were analyzed using descriptive statistics in SPSS-16 software. Results: There was no physical ABUSE and rejection, but the highest level of ABUSE was emotional negligence. The mean scores of financial ABUSES were less than 10%, authority negation less than 15%, financial neglect less than 20%, caring neglect and psychological ABUSE less than 25%, and emotional negligence less than 55% in both villages. Conclusion: It is suggested that the ABUSE level be measured using the elderly in homes and centers such as hospitals, nursing homes, etc. the injured elderly should be screened and receive necessary consultation and support services.